Comparison of Platelet Indices, Lymphocyte, and Systemic Inflammation Indices on Days 1 and 8 in Surviving and Non-Surviving COVID-19 Patients at Hasan Sadikin General Hospital, Bandung, Indonesia - Harti GF; Maulida SN; Susandi E; Fadjari TH; Sumardi U; Alisjahbana B; Wijaya I (Journal of Blood Medicine)
Gusti Fungani Harti,1 Syifa Nur Maulida,2 Evan Susandi,3 Trinugroho Heri Fadjari,1 Uun Sumardi,3 Bachti Alisjahbana,2,3 Indra Wijaya1 1Division of Hemato and Oncology Medic, Department of Internal Medicine, Hasan Sadikin General Hospital, Faculty of Medicine Universitas Padjadjaran, Bandung, Indonesia; 2Research Center for Care and Control of Infectious Disease, Universitas Padjadjaran, Bandung, Indonesia; 3Division of Tropical and Infectious Disease, Department of Internal Medicine, Hasan Sadikin General Hospital, Faculty of Medicine Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Indra Wijaya, Division of Hemato and Oncology Medic, Department of Internal Medicine, Hasan Sadikin General Hospital, Faculty of Medicine Universitas Padjadjaran, Pasteur No. 38, Bandung, West Java, 40161, Indonesia, Email indra.wijaya@unpad.ac.idPurpose: This study aimed to compare platelet count, platelet indices, lymphocyte, and systemic inflammation indices between surviving and non-surviving COVID-19 patients, measured at admission and on the eighth day of hospitalization.Patients and Methods: A retrospective cohort study was conducted on COVID-19 patients hospitalized at Hasan Sadikin General Hospital, Bandung, from March to December 2020. Patient characteristics and laboratory data were sourced from medical records and the Clinical Pathology Laboratory. Bivariate analysis was performed to determine the comparison of platelet indexes between Surviving and Non-Surviving COVID-19 patients depending on data distribution. Significantly correlated variables in Bivariate analysis were included in the ROC analysis, with the AUC used to identify optimal threshold values for laboratory parameters.Results: Data from 132 patients were analyzed, with 106 (80.3%) surviving and 32 (19.7%) not surviving. Non-surviving patients had lower platelet count, PLTCT, and lymphocyte levels but higher MPV and PDW compared to survivors. Receiver operating characteristic (ROC) analysis revealed that on day 1, lymphocytes had a higher area under the curve (AUC) than MPV. On day 8, lymphocytes had the highest AUC, followed by platelet count, MPV, PLTCT, and PDW.Conclusion: Platelet indices, lymphocyte counts, and systemic inflammation index have the potential to distinguish the severity of COVID-19.Keywords: mortality, platelet indices, thrombocytopenia, SII, NLR